Vaccinia Virus Expressing Interferon Regulatory Factor 3 Induces Higher Protective Immune Responses against Lethal Poxvirus Challenge in Atopic Organism - Pilna, Hana; Hajkova, Vera; Knitlova, Jarmila; Liskova, Jana; Elsterova, Jana; Melkova, Zora (Viruses, 2021)
Vaccinia virus (VACV) is an enveloped DNA virus from the Orthopoxvirus family, various strains of which were used in the successful eradication campaign against smallpox. Both original and newer VACV-based replicating vaccines reveal a risk of serious complications in atopic individuals. VACV encodes various factors interfering with host immune responses at multiple levels. In atopic skin, the production of type I interferon is compromised, while VACV specifically inhibits the phosphorylation of the Interferon Regulatory Factor 3 (IRF-3) and expression of interferons. To overcome this block, we generated a recombinant VACV-expressing murine IRF-3 (WR-IRF3) and characterized its effects on virus growth, cytokine expression and apoptosis in tissue cultures and in spontaneously atopic Nc/Nga and control Balb/c mice. Further, we explored the induction of protective immune responses against a lethal dose of wild-type WR, the surrogate of smallpox. We demonstrate that the overexpression of IRF-3 by WR-IRF3 increases the expression of type I interferon, modulates the expression of several cytokines and induces superior protective immune responses against a lethal poxvirus challenge in both Nc/Nga and Balb/c mice. Additionally, the results may be informative for design of other virus-based vaccines or for therapy of different viral infections.
Keywords: Immunity; Interleukin-1beta; Mice, Inbred BALB C; Vaccinia; Vaccinia virus; Gene Expression Regulation, Viral; mužské pohlaví; imunita; Mice; infekce vyvolané poxviry; vakcínie; replikace viru; regulace exprese virových genů; Viral Vaccines; interleukin-1beta; virové vakcíny; Gene Expression; zvířata; interferonový regulační faktor 3; interferon typ I; Skin; myši inbrední BALB C; myši; Poxviridae; exprese genu; Interferon Type I; virus vakcinie; Virus Replication; Interferon Regulatory Factor-3; kůže; Male; Poxviridae Infections; Animals